2006
DOI: 10.1111/j.1742-4658.2006.05410.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic iminosugar active‐site‐specific chaperones increase residual glucocerebrosidase activity in fibroblasts from Gaucher patients

Abstract: Gaucher disease is an autosomal recessive lysosomal storage disorder caused by the deficient activity of glucocerebrosidase. Accumulation of glucosylceramide, primarily in the lysosomes of cells of the reticuloendothelial system, leads to hepatosplenomegaly, anemia and skeletal lesions in type I disease, and neurologic manifestations in types II and III disease. We report herein the identification of hydrophilic active-site-specific chaperones that are capable of increasing glucocerebrosidase activity in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
98
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 36 publications
0
98
0
4
Order By: Relevance
“…While both treatments are effective in improving the hematologic and visceral symptoms in patients with mild, non-neuronopathic forms of the disease, their efficacy may be limited by their inability to cross the blood-brain barrier (ERT) or adverse side effects (SRT). Recent studies have demonstrated the ability of sugar analog inhibitors to increase the activity of mutant lysosomal enzymes in patient fibroblasts by acting as pharmacological chaperones [10][11][12][13][14][15]. As active site inhibitors, these compounds bind to the mutant enzymes and stabilize them in the ER, thereby preventing their ER-associated degradation and facilitating their folding and transport out of this compartment to lysosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While both treatments are effective in improving the hematologic and visceral symptoms in patients with mild, non-neuronopathic forms of the disease, their efficacy may be limited by their inability to cross the blood-brain barrier (ERT) or adverse side effects (SRT). Recent studies have demonstrated the ability of sugar analog inhibitors to increase the activity of mutant lysosomal enzymes in patient fibroblasts by acting as pharmacological chaperones [10][11][12][13][14][15]. As active site inhibitors, these compounds bind to the mutant enzymes and stabilize them in the ER, thereby preventing their ER-associated degradation and facilitating their folding and transport out of this compartment to lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have demonstrated the ability of iminosugars to increase the activity of mutant forms of GlcCerase [10][11][12][13][14][15]. We have recently reported that the iminosugar, isofagomine (IFG), enhances N370S GlcCerase activity by approximately 3-fold by facilitating its folding and transport out of the ER to lysosomes.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Cell-based activity and immunofluorescence assays have demonstrated an IFGdependent increase in lysosomal pools of enzymatically active N370S GCase. [7,8,16] Steet et al [8] proposed that IFG increases the exit of mutant GCase from the ER. Given that the kinetic properties of the mutant enzyme following treatment with IFG resembled those of the wild type enzyme, it was further proposed that the increased ER export occurred because of the stabilization of natively folded N370S GCase, which was induced by the formation of IFG-GCase complexes.…”
mentioning
confidence: 99%
“…A similar trend is seen in the L-ido-configured series. Again, GCS inhibitory potency increases with increasing N-alkyl substituent, and again, the N-alkyloxyalkyl derivatives (22)(23)(24)(25)(26)(27) outperform the N-alkyl species (10)(11)(12)(13)(14)(15). Head-to-head comparison of two stereoisomers from the two series reveals that in general the L-ido congener is the most potent GCS inhibitor.…”
mentioning
confidence: 99%
“…[14][15][16][17][18][19] Potent and selective GCS inhibitors thus hold considerable potential therapeutic value, and the development of such compounds is pursued by an increasing number of researchers worldwide. [20][21][22][23][24][25][26][27][28][29][30] In the search for selective GCS inhibitors, we give particular attention to the two known hydrolytic activities capable of hydrolyzing glucosylceramide, next to the aforementioned GBA1 and also the nonlysosomal glucosylceramidase or GBA2. As said, partially dysfunctional GBA1 is at the basis of Gaucher DOI: 10.1021/ml100192b |ACS Med.…”
mentioning
confidence: 99%